(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article discusses issues relating to religion tolerance and the identity of F.Gulen. Citing numerous historical examples on this subject the author emphasizes the fact that Islam as a religion of peace has always supported the inter-religious harmony and tolerance.